Suicide risk in the UK trans population and the role of gender transition in decreasing suicidal ideation and suicide attempt. Issue 4 (2nd December 2014) - Bailey, Louis; J. Ellis, Sonja; McNeil, Jay
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present findings from the Trans Mental Health Study (McNeil et al., 2012) – the largest survey of the UK trans population to date and the first to explore trans mental health and well-being within a UK context. Findings around suicidal ideation and suicide attempt are presented and the impact of gender dysphoria, minority stress and medical delay, in particular, are highlighted. Design/methodology/approach – This represents a narrative analysis of qualitative sections of a survey that utilised both open and closed questions. The study drew on a non-random sample (n=889), obtained via a range of UK-based support organisations and services. Findings – The study revealed high rates of suicidal ideation (84 per cent lifetime prevalence) and attempted suicide (48 per cent lifetime prevalence) within this sample. A supportive environment for social transition and timely access to gender reassignment, for those who required it, emerged as key protective factors. Subsequently, gender dysphoria, confusion/denial about gender, fears around transitioning, gender reassignment treatment delays and refusals, and social stigma increased suicide risk within this sample. Research limitations/implications – Due to the limitations of undertaking research with this population, the research is not demographically representative. Practical implications – The study found that trans people are most at risk prior to social and/or medical transition and that, in many cases, trans people who require access to hormones and surgery can be left unsupported for dangerously long periods of time. The paper highlights the devastating impact that delaying or denying gender reassignment treatment can have and urges commissioners and practitioners to prioritise timely intervention and support. Originality/value – The first exploration of suicidal ideation and suicide attempt within the UK trans population revealing key findings pertaining to social and medical transition, crucial for policy makers, commissioners and practitioners working across gender identity services, mental health services and suicide prevention.